Allelochemicals of the phenoxazinone class act at physiologically relevant concentrations. (3rd May 2016) - Venturelli, Sascha; Petersen, Sebastian; Langenecker, Tobias; Weigel, Detlef; Lauer, Ulrich M.; Becker, Claude
ABSTRACT: Plants compete with their neighbors via the release of chemical compounds into the rhizosphere. These phytotoxins originate from a series of secondary metabolites and can be processed further by soil-living microorganisms before exerting their activity on the target plant. To determine the molecular mode of action and the physiological relevance of potential phytotoxins, it is important to simulate true-to-life conditions in laboratory experiments, for example by applying physiologically relevant concentrations. Here, we report on an improved experimental setting to study the function of allelochemicals of the benzoxazolinone class. By adjusting the solvent and the application of the chemicals, we reduced by more than 2fold the concentration that is necessary to induce growth defects in the model plant Arabidopsis thaliana.